ANALISIS PENGARUH PEMASARAN MEDIA SOSIAL, DUTA MEREK, DAN CITRA MEREK TERHADAP PENGAMBILAN KEPUTUSAN PEMBELIAN (Studi Empiris Pada Konsumen Produk Y.O.U Beauty di Kota Semarang) - Varentiningtyas, Widya; Hidayati, Retno (Faculty of Economics and Business Diponegoro University, 2024)
ABSTRACT The beauty industry is currently experiencing rapid growth. Y.O.U. Beauty is one of the alternative choices of skincare and cosmetic products for consumers. This study aims to analyze the effect of social media marketing, brand ambassadors, and brand image on purchasing decisions for consumers of Y.O.U. Beauty products in Semarang City. The population used in this study were consumers of Y.O.U. Beauty products in Semarang City. In this study, data collection methods were carried out through questionnaires from a sample of 150 respondents using non-probability sampling and purposive sampling techniques. Then, the data was processed and analyzed using multiple linear regression analysis techniques with SPSS (Statistical Package for Social Science) software version 26. The results showed that social media marketing, brand ambassadors, and brand image had a significant positive effect on purchasing decisions for consumers of Y.O.U. Beauty products in the city of Semarang, so all hypotheses are determined between social media marketing, brand ambassadors, and brand image on purchasing decisions for consumers of Y.O.U. Beauty products in Semarang City were accepted.